(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
The electrical engineer Nikola Tesla is one of the scientists who made the most important contributions to the development of electrical science and technology in the last 100 years. During its 86 years of life, the majority as a resident of the USA, dedicates them to subjects as diverse as electricity and electromagnetism, among others, anticipating in several decades the physics of their time. He is considered the father of alternating electricity flow, with granted patents, some of them after his death. His life is fascinating, not only for his inventions but for the stories and stories that surround him. It stars in the famous period known as the Battle of the Electricity flow, whose opponent was the renowned Thomas Alva Edison, an environment that has served as a script for various documentaries and films. The purpose of this paper is to describe part of its history and, especially, of this famous period. We hope that readers will be as fascinated with the life and work of this character, as many of us are when we appreciate the invaluable legacy of their technological developments.